A saúde do pescador artesanal de Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
Introduction: Artisanal fishing is understood as a commercial fishing modality, which is characterized by poorly mechanized work, autonomously and in a family economy regime. The fishing activity exposes its workers to innumerable risks of illnesses and accidents. Considering the great economic, social and cultural importance of this worker for the region of Baixo Amazonas-Pará, as well as the absence of official local health indicators specific to this professional category, this study was carried out. Objective: Given the risks inherent to the profession, this research aimed to analyze the health conditions of artisanal fishermen in the municipality of Santarém. Methodology: For this purpose an empirical research was carried out, of a descriptive and analytical nature, of the transversal, exploratory type, with a quantitative and qualitative approach. Its target audience was artisanal fishermen (n = 111), affiliated to the Colony of Fishermen Z-20 (CP Z-20), based in the municipality of Santarém-Pará. As instruments of data collection, questionnaires, physical evaluations and semi-structured interviews were used. The research was approved by the Human Research Ethics Committee. Data were collected between the years 2018 and 2019. Results: It was possible to observe that the profile of artisanal fishermen was composed of men, of working age, married, with an average of two children per family, their own home, residence in the floodplain regions. municipality, with an average income of one minimum wage, owners of their vessels and fishing harnesses. As for health aspects, a large number of fishermen were hypertensive, were overweight or with grade I obesity, and had complaints of pain or discomfort in their back regions, in the last twelve months and seven days. Its activity has been classified ergonomically, by the RULA Software, as a serious effort, requiring immediate intervention for correction. Conclusion: With the completion of the study it was possible to conclude that artisanal fishermen in the municipality of Santarém are exposed to physical, ergonomic and accident risks, related to the nature of their work occupation. And that many already had osteomuscular disorders installed in the spine, of a chronic and acute nature. As well as having risk factors for cardiovascular diseases, such as high blood pressure and body mass index (BMI) above expected. They conceived the concept of health as that linked to the absence of disease, and that the individual's well-being is related to his optimistic posture in the face of life's difficulties, with the expression of his resilience in the face of the adversities that they considered inherent in the fisherman's routine in activity.
Keywords: Saúde Ocupacional; Qualidade de Vida; Pesca Artesenal; Pescadores